Ihtikar In The Social Frame: A Sociological Analysis Of Economic Dynamics And Their Impact In The Contemporary Contex - Islah Siregar, Muhamad; Arifin, Tajul; Abdal, Abdal (Yayasan Mentari Madani, 2024)
This research deepens sociological studies of the phenomenon of ihtikar, an economic practice in which individuals or groups hoard goods or resources with the intention of increasing value or prices in the market. Using a sociological approach, this study aims to understand the impact of ihtikar on social structure, conflict, and social interaction in society. Analysis of the distribution of resources in the context of ihtikar reveals the dynamics of power and inequality that may arise within society. Class struggle, as a result of ihtikar, takes center stage to understand how this practice can deepen social inequality. The interconnectedness of ihtikar with social interactions and market dynamics provides deeper insight into how this economic behavior affects relationships between individuals and impacts daily life. economics, and culture to understand ihtikar as a phenomenon involving complex dynamics in society. The results of this study are expected to contribute to our understanding of the role of ihtikar in shaping social structure, conflict, and social interaction, as well as provide a foundation for policy debates and social actions that are more effective in addressing their impacts